Horizontally Acquired Genes Are Often Shared between Closely Related Bacterial Species - Bolotin, Evgeni; Hershberg, Ruth (Frontiers in Microbiology, 2017)
Horizontal gene transfer (HGT) serves as an important source of innovation for bacterial species. We used a pangenome-based approach to identify genes that were horizontally acquired by four closely related bacterial species, belonging to the Enterobacteriaceae family. This enabled us to examine the extent to which such closely related species tend to share horizontally acquired genes. We found that a high percent of horizontally acquired genes are shared among these closely related species. Furthermore, we demonstrate that the extent of sharing of horizontally acquired genes among these four closely related species is predictive of the extent to which these genes will be found in additional bacterial species. Finally, we show that acquired genes shared by more species tend to be better optimized for expression within the genomes of their new hosts. Combined, our results demonstrate the existence of a large pool of frequently horizontally acquired genes that have distinct characteristics from horizontally acquired genes that are less frequently shared between species.